1978
DOI: 10.1161/01.cir.58.4.679
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of bundle branch block complicating acute myocardial infarction. 1. Clinical characteristics, hospital mortality, and one-year follow-up.

Abstract: To provide an understanding of the clinical characteristics of patients with acute myocardial infarction (MI) and bundle branch block, experience from five centers was accumulated. Patients in whom bundle branch block first appeared after the onset of cardiogenic shock were excluded. In 432 patients, the most common types of block were left (38%) and right with left anterior fascicular block (34%). In 42% of the patients, bundle branch block was new. Progression to high degree (second or third degree) atrioven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
2
8

Year Published

1978
1978
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(80 citation statements)
references
References 46 publications
5
62
2
8
Order By: Relevance
“…[1][2][3][4][5][6][7] To facilitate the optimal use of prophylactic temporary pacing, it is necessary to identify those parameters which determine the risk of development of sudden advanced AV block.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] To facilitate the optimal use of prophylactic temporary pacing, it is necessary to identify those parameters which determine the risk of development of sudden advanced AV block.…”
mentioning
confidence: 99%
“…In several studies on chronic and acute CAD, LBBB was found to be an excellent predictor of mortality and events [20][21][22][23][24] (Table 2). In 681 patients with acute myocardial infarction (AMI) enrolled in the Thrombolysis and Angioplasty in Myocardial Infarction (TAMI) 9 and Global Utilization of Streptokinase and t-PA for Occluded Arteries (GUSTO) 1 protocols, 25 the incidence of LBBB was found to be 7%.…”
Section: Left Bundle-branch Block and Risk Stratification In Heart DImentioning
confidence: 99%
“…2,9,12 Complete BBB, left or right, on electrocardiogram at presentation occurs in a wide range of 8% to 23% of patients with AMI and represents an independent important predictor of in hospital complications and poor survival. [1][2][3][4][5][6][7][8][9][10][11][12][13] New BBB usually expresses a large infarction, frequently accompanied by heart failure, complete AV block, arrhythmia and high mortality rates. 10 In the present study, an attempt has been made to assess clinical characteristics and short term prognostic significance of BBB in acute MI, with respect to its location, time of appearance and association with complications.…”
Section: Introductionmentioning
confidence: 99%